Uso de tic y logros de aprendizaje en el área de matemática en estudiantes del quinto ciclo de primaria de la IE N° 61014 Horacio Zevallos Gamez de Iquitos en el año 2024 - Rosales Linares, Lady Esther (2025)
The aim of this study was to determine the relationship between use of ICT level and the learning achievement level in mathematic area levels of the fifth cycle students at the primary level of the educational institution N° 61014 “Horacio Zevallos Gamez, of Iquitos in 2024. Methods: It was applied a questionnaire to 130 children. The study was descriptive – relational and design was not experimental. To determine the relationship it used the non-parametric statistical test Spearman Rho. The test Rho = 0.263, with a value p=0,003. Conclusion: there is a positive and significative relationship between use of ICT level and the learning achievement level in mathematic levels of the fifth cycle students at the primary level of the educational institution N° 61014 “Horacio Zevallos Gamez, of Iquitos in 2024.